(untitled) (Innovative Teaching and Learning Journal, 2023)
Nowadays, the use of social media is increasingly widespread and pervasive, especially among students. Various useful information and resources can be obtained quickly due to the existence of social media. Recognizing the importance and the need for social media usage, this study aims to identify the perceptions of final-year students in the Technical and Vocational Education and Training (TVET) field at the School of Education, Universiti Teknologi Malaysia, regarding the use of social media in teaching and learning, specifically Twitter, Youtube, and Instagram. A quantitative approach was employed in this study, involving a sample of 75 respondents who completed a questionnaire to answer the research questions. Data analysis was performed using the Statistical Package for Social Science (SPSS) version 26 to obtain minimum values, percentages, and frequencies for the research questions. Regression analysis was also utilized to examine the effects of social media usage on students’ skills, communication, and instructional content. Overall, the findings indicate that the ’Youtube’ platform had a more positive perception in its use as a teaching media compared to ’Facebook’ and ’Twitter’ platforms. Additionally, the study reveals that the use of social media has a positive impact on improving students’ skills (42.9%), communication (60.7%), and instructional content (51.5%). Abstrak: Penggunaan media sosial pada masa kini semakin luas dan menyeluruh terutamanya di kalangan pelajar. Pelbagai maklumat dan informasi yang bermanfaat boleh diperolehi dalam masa singkat setelah kewujudan media sosial ini. Melihat kepada kepentingan dan keperluan penggunaan media sosial, kajian ini dijalankan bagi mengenalpasti persepsi pelajar tahun akhir bidang pendidikan teknikal dan vokasional (TVET) di Sekolah Pendidikan, Universiti Teknologi Malaysia terhadap penggunaan media sosial dalam pengajaran dan pembelajaran yang merangkumi Twitter, Youtube dan Instagram. Pendekatan kuantitatif telah digunakan dalam kajian ini yang melibatkan sampel seramai 75 responden melalui satu soal selidik bagi menjawab persoalan kajian. Penganalisisan data dibuat dengan menggunakan perisian Statistical Package for Social Science SPSS Statistics (SPSS) versi 26 bagi mendapatkan nilai min, peratusan dan kekerapan bagi persoalan. Analisis regresi pula telah digunakan bagi melihat kesan penggunaan media sosial kepada kemahiran pelajar, komunikasi pelajar dan kandungan pelajaran. Secara keseluruhannya, dapatan kajian mendapati bahawa platform ‘Youtube’ mempunyai persepsi yang lebih baik dalam penggunaannya sebagai media pengajaran berbanding platform ‘Facebook’ dan ‘Twitter’. Selain itu, kajian juga menunjukkan bahawa, penggunaan media sosial memberikan impak positif terhadap peningkatan kemahiran pelajar (42.9%), komunikasi pelajar (60.7%) dan kandungan pelajaran (51.5%).